2020
DOI: 10.1088/1402-4896/abd364
|View full text |Cite
|
Sign up to set email alerts
|

MHD stagnation point flow of hybrid nanofluid over a permeable cylinder with homogeneous and heterogenous reaction

Abstract: This investigation is addressed to examine the comparative consequence of thermal radiation and heat generation/absorption in steady three-dimensional MHD (Magneto-hydrodynamics) stagnation point flow of (MWCNTs + Cu/engine oil) hybrid nanofluid over a porous circular cylinder. Flow via thermal slip effect is inspected. Also, the impact of both homogeneous/heterogeneous (h–h) chemical reactions are considered for explanation of mass transportation characteristics. Here, a kind of hybrid nanofluid including MWC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…To investigate the solution's stability, a small perturbation also needs to be taken into consideration in which f (η) = f 0 (η) and θ(η) = θ 0 (η). Moreover, upon differentiating Equation (19) and equating it to Equations ( 16) and ( 17) with τ = 0 yields the linearized equations given below:…”
Section: Solutions On Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the solution's stability, a small perturbation also needs to be taken into consideration in which f (η) = f 0 (η) and θ(η) = θ 0 (η). Moreover, upon differentiating Equation (19) and equating it to Equations ( 16) and ( 17) with τ = 0 yields the linearized equations given below:…”
Section: Solutions On Stability Analysismentioning
confidence: 99%
“…Furthermore, [18] examines the lower stagnation point flow over a horizontal circular cylinder of brinkman-viscoelastic fluid. [19] explore the use of homogeneous and heterogenous reaction over a permeable cylinder. The work on stagnation flow with the effect of slip continued to be investigated by [20].…”
Section: Introductionmentioning
confidence: 99%
“…Dual solutions were found in this study, and the stability analysis identifies the first solution as stable and meaningful. Other studies on stagnation point flow of hybrid nanofluid were carried out by Jakeer and Reddy (2020), Zainal et al (2020b), Nasir et al (2020), Alghamdi et al (2021), Khan et al (2021b), Arani and Aberoumand (2021), Waini et al (2022b), Jawad et al (2022), Kamal et al (2022) and Zainal et al (2022). Very good references on nanofluids and hybrid nanofluids can be found in the books by Das et al (2008), Nield and Bejan (2017), Shenoy et al (2016) and Merkin et al (2021).…”
Section: Introductionmentioning
confidence: 98%
“…Rehman et al [20] examined the nanofluid motion and energy transmission of at a stagnation on a continuously extending medium affected by the magnetization. The mathematical formulation of nanoliquid stagnation motion associated with energy and mass transport on a rolling surface with slip velocity was explored by Khashi'ie et al [21] Nasir et al [22] explored the effects of radiation and heat source in a 3D magnetohydro-dynamics stagnation flow of engine oil based MWCNTs+Cuhybrid nanofluid through a permeable spherical tube. Recently some other investigations such as Waini et al, [23,24] may be reported in the literature to visualize the stagnation flow of fluid in different geometries under various conditions.…”
Section: Introductionmentioning
confidence: 99%